Development of a control system for artificially rehabilitated limbs: A review - Bhuiyan, M.S.H.; Choudhury, I.A.; Dahari, M. (SPRINGER, 233 SPRING ST, NEW YORK, NY 10013 USA, 2015)
Development of an advanced control system for prostheses (artificial limbs) is necessary to provide functionality, effectiveness, and preferably the feeling of a sound living limb. The development of the control system has introduced varieties of control strategies depending on the application. This paper reviews some control systems used for prosthetics, orthotics, and exoskeletons. The advantages and limitations of different control systems for particular applications have been discussed and presented in a comparative manner to help in deciding the appropriate method for pertinent application.